2023
DOI: 10.3390/ijms24031905
|View full text |Cite
|
Sign up to set email alerts
|

TAT Nanobody Exerts Antiviral Effect against PRRSV In Vitro by Targeting Viral Nucleocapsid Protein

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is caused by the PRRS virus (PRRSV), which has brought huge economic losses to the pork industry worldwide since its first discovery in the late 1980s in North America. To date, there are no effective commercial vaccines or therapeutic drugs available for controlling the spread of PRRSV. Due to their unique advantages of high affinity and high specificity, nanobodies (Nbs) have received increasing attention in the process of disease diagnosis and treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, NPC is expressed in prokaryotic system while most therapeutic candidates for humans are prepared in eukaryotic systems, which offers the cost-effective advantage for NPC application. Existing studies have shown 20 µM TAT-nanobody exerts antiviral effect against PRRSV in vitro by targeting viral N protein [ 47 ]; TAT-Nb6 significantly inhibited the propagation of PRRSV SD16 at 30 µM [ 48 ]. These studies have shown that the working concentration of NPCs is within a reasonable range.…”
Section: Discussionmentioning
confidence: 99%
“…However, NPC is expressed in prokaryotic system while most therapeutic candidates for humans are prepared in eukaryotic systems, which offers the cost-effective advantage for NPC application. Existing studies have shown 20 µM TAT-nanobody exerts antiviral effect against PRRSV in vitro by targeting viral N protein [ 47 ]; TAT-Nb6 significantly inhibited the propagation of PRRSV SD16 at 30 µM [ 48 ]. These studies have shown that the working concentration of NPCs is within a reasonable range.…”
Section: Discussionmentioning
confidence: 99%